Integral Logistic Structure: Developing Customer-oriented Goods Flow - ARGELO, S.M., GENSEEN, R.D.M; [et all.] (Industrial Press Inc., 1991)
Integral Logistic Structure: Developing Customer-oriented Goods Flow